Shared waters, same standards – The Baltic Sea e-Nav project: A partnership for the future of marine navigation - Hell, Benjamin; Wallhagen, Magnus; Westfeld, Patrick; Hohwü-Christensen, Sophie; Mustaniemi, Rainer; Värre, Antti; Harper, James (The International Hydrographic Review, 2025)
In order to deploy the first layers of S-100 based navigation products in the Baltic Sea, and do so in a regionally harmonized manner, the Hydrographic Offices involved are partnering with academia and industry in the Baltic Sea e-Nav project. To unlock the full potential of the S-100 paradigm shift towards e-navigation, there is a need for transnational collaboration to build capacity and ensure seamless, harmonized products. In addition, the project will test S-100 products from an end-user perspective to ensure the most relevant and useable navigation data possible. The recently started project will continue until 2026 and is co-financed by the EU Interreg Baltic Sea Region programme.